RAPID RESOLUTION LIQUID CHROMATOGRAPHY METHOD FOR DETERMINATION OF CHLOROGENIC ACID IN ECHINACEA EXTRACTS - Velkoska-Markovska, Lenche; Petanovska-Ilievska, Biljana; Mihajlovski, Angel (University Ss. Cyril and Methodius in Skopje, 2018)
This study presents a development and validation of a new, fast, efficient and cost effective reversed-phase rapid resolution liquid chromatography (RP-RRLC) method for determination of chlorogenic acid in echinacea extracts. The optimum separation with symmetrical peak shape and good index purity of the analyte was achieved on a Poroshell 120 EC-18 (50 mm x 3 mm; 2.7 µm) analytical column, mobile phase consisted of acetonitrile/(water with 1 % phosphoric acid), (10/90, V/V)in isocratic elution with flow rate of 1 mL/min and UV diode-array detection (UV-DAD) at 325 nm. The developed method was validated by testing specificity, selectivity, linearity, precision, accuracy, limit of detection (LOD) and limit of quantification (LOQ). The calibration curve of chlorogenic acid followed Beer’s law within the range 28.97 ng - 362.19 ng (R2 = 0.9994). The LOD was 0.29 pg, while LOQ was 0.96pg. The intra-day precisions was evaluated for the retention time, peak area and peak height and the calculated values for relative standard deviations (RSD) were 0.21 %, 0.11 % and 0.22 %, respectively. The mean recoveries ranged from 98.75 to 104.63 % and RSD was less than 0.23 %. The developed method was successfully applied for identification and quantification of chlorogenic acid in three samples of echinacea extracts, taken from local pharmacies.
Keywords: RP-RRLC, UV-DAD, method development, validation